2012
DOI: 10.5963/lsmr0201001
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Activity of Aqueous Extracts of Some Medicinal Plants Wild Growing in Southern Tunisia

Abstract: . Given these results, we can say that the consumption of these extracts could have preventive and curative benefits against several diseases. People suffering from stomach problems or high blood pressure should show great concerns to it because of the acidity and relatively high sodium content of these extracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
4
2
Order By: Relevance
“…1). The content of total phenols and flavonoids, observed in our study, were higher than that reported for samples from the southern part of Tunisia [29,30] or for other Artemisia species such as A. annua, A. arborescens, A. ludoviciana, A. oleandica, A. princeps and A. stelleriana, [31] and Artemisia vulgaris. [32] The contents and the composition of total phenolic and flavonoid of A. herba-alba extracts varied according to plant origin, the solvent of extraction and the analytical method used.…”
Section: Phenolic Content and Compositioncontrasting
confidence: 87%
“…1). The content of total phenols and flavonoids, observed in our study, were higher than that reported for samples from the southern part of Tunisia [29,30] or for other Artemisia species such as A. annua, A. arborescens, A. ludoviciana, A. oleandica, A. princeps and A. stelleriana, [31] and Artemisia vulgaris. [32] The contents and the composition of total phenolic and flavonoid of A. herba-alba extracts varied according to plant origin, the solvent of extraction and the analytical method used.…”
Section: Phenolic Content and Compositioncontrasting
confidence: 87%
“…It seems that foliage from shrubs that grow in semiarid regions contains K as lower levels from costal and this not accordance with [31]. In this study the contents of Na are lower than those reported in (Abdullah, 2013) study, which it was (0.48 ppm) but they are lower than result found in [32] study (7.95 ppm).…”
Section: Juniperus Phoenicea Lcontrasting
confidence: 83%
“…DPPH is a stable nitrogen-centered free radical, the color of which changes from violet to yellow upon Facciola (1990) reduction by either the process of hydrogen-or electron donation (Dehpour et al, 2009). The procedure adopted by Wong et al (2006) and modified by Akrout et al (2012) was used. Different concentrations of extracts (0.125 to 5 mg/ml) and standard [ascorbic acid (20 to 100 µg/ml) (Merck Co. (Germany)) were prepared (MeE for methanol extract, and AqE for distilled water extract).…”
Section: Antioxidant Activitymentioning
confidence: 99%